Characterization of biodegradable composite based on polycaprolactone/starch reinforced with sugarcane bagasse microfibrillated cellulose - Jimat, Dzun Noraini; Sulaiman, Sarina; Ariffin, Faridah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Biodegradable polymers have been extensively studied in order to substitute the synthetic polymers since they are non-biodegradable which is harmful to environment. Polycaprolactone (PCL) could be a good candidate to substitute synthetic polymer since it can be slowly degraded by microbes. PCL was synthesized by ring-opening polymerization of -caprolactone with stannous octoate as catalyst. To improve the mechanical strength of PCL, it was reinforced with microfibrillated cellulose (MFC) and starch acts as filler. MFC was extracted from sugarcane bagasse (SCB) through chemo-mechanical treatments. Characterizations of the PCL-starch composite reinforced with SCB-MFC with respect to its morphology and structural changes were evaluated. In this study, amount of tapioca starch was fixed at 40%. Meanwhile, the composition of SCB-MFC and PCL were varied 50% to 58% and 2% to 10% respectively. Initial observation from microscopy images showed that there were significant changes of morphology of PCL after adding starch and SCB-MFC. The surface of biocomposite PCL-starch-SCB-MFC was quite uniform and smooth with less 5% of SCB-MFC. However, fine aggregates was observed on the sample with 10% of MFC-SCB due to the presence of sugarcane bagasse microfibril cellulose.